'Stakeholder' and 'resource' labelled employee treatment practices and firm performance - an integrative review and implications for future research. (5th May 2022) - Bhatt, Prachi; Joshi, Himanshu
Businesses have grown out of the traditional firm-employee relationships into appreciating employees as key 'stakeholder' instead of 'resource'. However, research regarding how an approach underlying employee treatment practices would serve firms' interest, remains largely incoherent. The paper through an integrative review synthesises relevant and related management literature scattered across various knowledge domains, i.e., stakeholder theory, organisational theory, resource-based theory, agency-cost theory. The paper discusses and offers propositions related to how 'resource-based' and 'stakeholder-based' approaches of employee treatment would influence perceived organisational support and perceived organisational justice by employees, thus impacting firm performance. Viewpoints differing from stakeholder perspective, which influence related management decisions, are also discussed. This study emphasises 'stakeholder' approach of management's decisions as proactive, inclusive and as a sustainable approach for employee treatment. It further stimulates future research in what is still largely missing, an integration of different perspectives for refinement of existing theories.